The enduring appeal of "Forever Young": A critical discourse analysis - Barans Irawan Palangan (Jurnal CULTURE (Culture, Language, and Literature Review), 2024)
This study applies critical discourse analysis (CDA) to Alphaville’s iconic song “Forever Young,” exploring how its lyrics have been recontextualized in contemporary social media trends. Recently, the song has gained popularity as a background for posts that honor deceased loved ones, celebrate moments of happiness, and highlight the contrast between youthful and aging appearances. This research aims to delve into the deeper meanings and societal implications embedded within the song’s lyrics, which span themes of youth, aging, and the desire for immortality. The study reveals how the song reflects and reinforces societal ideals about youth while marginalizing other life stages, especially old age, through three levels of analysis—micro-level (focusing on individual words and phrases), meso-level (considering the social context, and the song’s impact), and macro-level (examining broader societal discourses)—. It highlights the song’s exploration of the transience of life and the universal human longing for permanence. These themes resonate strongly with the prevalent social media trends that often celebrate youth and memorialize it in posts and tributes. The findings suggest that “Forever Young” serves as a personal reflection on the passage of time and a commentary on societal views of aging, vitality, and the unyielding pursuit of youth. It uncovers how the song has become a powerful cultural symbol, contributing to the ongoing digital conversation around the valorization of youth and the depreciation of the complexities associated with aging.